Odpowiedź :
Odpowiedź:
a) 5x + (2x - 7) - 9x - (-3x + 8) +20 - 8x =
5x + 2x - 7 - 9x + 3x - 8 + 20 - 8x =
-7x + 5
b) -5x + (-2y + 4x)-(7x-8y) - x + (2-6y) =
-5x - 2y + 4x -7x + 8y - x + 2 - 6y =
-9x + 2
c) -92-(4-32) - 5y- (-77 + 8y) + (-2y-7) =
- 92 + 28 - 5y + 77 - 8y + -2y - 7 =
13 - 7 - 15y
6 - 15y
a) 5x + (2x - 7) - 9x - (-3x + 8) +20 - 8x = 5x + 2x - 7 - 9 + 3x - 8 + 20 - 8x = 2x + 4
b) -5x + (-2y + 4x) - (7x - 8y) - x + (2 - 6y) = -5x - 2y + 4x - 7x + 8y - x + 2 - 6y = -9x + 2
c) -92 - (4 - 32) - 5y - (-77 + 8y) + (-2y - 7) = -92 - 4 + 32 - 5y + 77 - 8y - 2y - 7 = -15y + 6